ISLAM, BUDAYA KORUPSI DAN GOOD GOVERNANCE - Fawaid, Ahmad (Institut Agama Islam Negeri Madura)
AbstractThe phenomenon and corruption action still becomes a fact that cannot be finished. One of causes is mentality of the world. It makes the cause why corruption becomes a massive culture. Beside restraining orientation of the world, good governance must become the priority. The result is that corruption does not become the culture anymore, and slowly but sure, it can be eliminated, or at least it can decrease.Kata-kata kuncikorupsi, budaya korupsi, indeks persepsi korupsi, good governance